REGIONAL POLICY IN THE CONDITIONS OF DIGITAL TRANSFORMATION OF ECONOMY - G. Lagutin; E. Kharchenko (Вестник Северо-Кавказского федерального университета)
The article presents the directions of the formation of the regional policy as an essential element of the government economic policy which includes legislative, administrative and economic activities. It is noted that the main goal for the Kursk region is the creation of a self-contained, innovative developing, strongholds region which combines regional, interregional, national and international interests in dealing with the strategic tasks of the socio-economic and the territorial development.